MENGINGAT KEMBALI BUDAYA TIONGHOA DI KOTA TANGERANG MELALUI INTERAKTIF GALERI DENGAN KONSEP AXIS INTERGRATED CIRCULATION - Haryono, Erick Prasetya; Husin, Denny (Jurusan Arsitektur dan Perencanaan, 2024)
The disappearance of Chinese culture in Tangerang can be traced back to the main beliefs of the Cina Benteng community, namely Confucianism, and its relationship with other religious and cultural groups. The term